1989
DOI: 10.2527/jas1989.671177x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships Between Sex and Exogenous Growth Hormone Administration on Performance, Body Composition and Protein and Fat Accretion of Growing Pigs

Abstract: Forty-five pigs with an average initial live weight of 60 kg were used to investigate the effects of daily exogenous porcine pituitary growth hormone administration at two dose levels (pGH; 0, excipient buffer injected, and 100 micrograms.kg-1.d-1) for a 31-d period on the performance and body composition of boars, gilts and barrows allowed to consume feed ad libitum. Excipient boars consumed less feed, exhibited faster and more efficient growth (P less than .01) and produced less fat and more protein and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
47
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 15 publications
13
47
2
Order By: Relevance
“…These findings are in line with recent studies reporting a tendency towards lower ADG for entire males reared in group compared to castrates (Dunshea et al, 2001;D'Souza and Mullan, 2002;Suster et al, 2006). Contrarily, some previous studies reported that entire male pigs had higher ADG and better FCR than castrates (Whittemore et al, 1988;Campbell et al, 1989;Dunshea et al, 1993). This might be surprising as the genetic growth potential was markedly improved in the last decade due to breeding efforts.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with recent studies reporting a tendency towards lower ADG for entire males reared in group compared to castrates (Dunshea et al, 2001;D'Souza and Mullan, 2002;Suster et al, 2006). Contrarily, some previous studies reported that entire male pigs had higher ADG and better FCR than castrates (Whittemore et al, 1988;Campbell et al, 1989;Dunshea et al, 1993). This might be surprising as the genetic growth potential was markedly improved in the last decade due to breeding efforts.…”
Section: Discussionsupporting
confidence: 90%
“…In a recent study comparing the growth performance of group-penned entire males and barrows, we reported -E-mail: Giuseppe.Bee@alp.admin.ch that, entire males grew slower (774 v. 830 g/day), consumed less feed (1.88 v. 2.23 kg/day) but were more feed efficient (2.43 v. 2.69 kg feed/kg gain) than barrows (Pauly et al, 2008). The lower average daily feed intake (ADFI) and lower average daily gain (ADG) of entire males compared to barrows, is in agreement with Lawlor et al (2003) and Dunshea et al (2001) but in contrast to earlier results reported by Campbell et al (1989) and Dunshea et al (1993). Based on earlier observations (Pauly et al, 2008), it is unclear whether appetite is limiting or feed intake is low because of increased aggressive behaviour of group-penned entire males.…”
Section: Introductionsupporting
confidence: 89%
“…its genotype), which can be measured as described by Ferguson & Gous (1993). Any changes in the PR,,, due to administration of exogenous porcine somatotropin (for example Campbell et al 1989), or other pharmacological agents, are seen as changes in the values of these two variables, in particular the value of B.…”
Section: Rates Of Empty-body Change Under Non-limiting Conditionsmentioning
confidence: 99%